1999
DOI: 10.1074/jbc.274.47.33213
|View full text |Cite
|
Sign up to set email alerts
|

pH Regulation in the Intracellular Malaria Parasite, Plasmodium falciparum

Abstract: The mechanism by which the intra-erythrocytic form of the human malaria parasite, Plasmodium falciparum, extrudes H ؉ ions and thereby regulates its cytosolic pH (pH i ), was investigated using saponin-permeabilized parasitized erythrocytes. The parasite was able both to maintain its resting pH i and to recover from an imposed intracellular acidification in the absence of extracellular Na ؉ , thus ruling out the involvement of a Na ؉ /H ؉ exchanger in both processes. Both phenomena were ATPdependent. Amiloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
239
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(261 citation statements)
references
References 42 publications
20
239
0
2
Order By: Relevance
“…6). These results showed that chloroquine stimulated a H + extrusion response with an EC 50 of 16 µM in P. chabaudi, using plasma membrane mechanisms to recover the intracellular pH (Saliba & Kirk 1999).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…6). These results showed that chloroquine stimulated a H + extrusion response with an EC 50 of 16 µM in P. chabaudi, using plasma membrane mechanisms to recover the intracellular pH (Saliba & Kirk 1999).…”
Section: Discussionmentioning
confidence: 76%
“…Fig 5 shows spectrofluorimetric measurements of calcium release by Thg (10 µM) with parasites previously incubated (15 min at 37 o C) with different concentrations of chloroquine and artemisinin (0-80 µM) in a high calcium ex- The results show that previous parasite incubation with chloroquine or artemisinin leads to a dose-dependent reduction of total amount of calcium release by thapsigargin. When parasites are exposed to chloroquine, the cytosolic pH decrease as a result of extrusion of H + from acidic compartments and the parasites (P. falciparum) try to restore the cytosolic pH level using plasma membrane mechanisms (Saliba & Kirk 1999, Marchesini et al 2000, Saliba et al 2003. By using microphysiometry we showed that addition of chloroquine to P. chabaudi at the trophozoite stage led to a dose-dependent increase in the extracellular acidification rate (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The malaria parasite is wholly reliant on glycolysis for the generation of ATP (Sherman, 1998) and ATP is depleted rapidly when parasites are incubated in a glucose-free medium (Saliba and Kirk, 1999). Whereas in ATP-replete parasites the uptake of adenosine (10 µ M) reached a distribution ratio of 4-5 within a few seconds and increased more slowly thereafter (as in Fig.…”
Section: Nucleoside Uptakementioning
confidence: 97%
“…Every 4-6 days, a proportion of the ring-stage parasites not required to propagate the culture were treated with saponin essentially as described previously (except that centrifugation was performed at 12 000 g) (Saliba and Kirk, 1999) in order to remove erythrocyte haemoglobin. Genomic DNA was then extracted from the isolated parasites using a DNeasy Plant Mini Kit (Qiagen), and stored at -20∞C.…”
Section: Genomic Dna Extractionmentioning
confidence: 99%